Go for Growth : Five Paths to Profit and Success : Choose the Right One for You and Your Company - Tomasko, Robert M. (New York John Wiley & Sons, INC., 1996)
Include Index
Keywords: Reengineering (Management) -- Success in Business -- Organisatieverandering -- Business -- Innovation